Conjugated polymer acceptors based on fused perylene bisimides with a twisted backbone for non-fullerene solar cells. Issue 21 (5th May 2017) - Jiang, Xudong; Xu, Yunhua; Wang, Xiaohui; Yang, Fan; Zhang, Andong; Li, Cheng; Ma, Wei; Li, Weiwei
Abstract : Electron acceptors based on fused perylene bisimide dimers with a twisted backbone were developed to show high electron mobility and isotropic crystalline properties, resulting in high power conversion efficiencies in non-fullerene solar cells. Abstract : In this work, we present a new strategy to use fused and twisted conjugated backbones to construct conjugated small molecules and polymers as electron acceptors for non-fullerene solar cells. The new conjugated materials containing binary perylene bisimide (PBI) units linked with coplanar thieno[3, 2- b ]thiophene (as trans -PBI) or twisted thieno[2, 3- b ]thiophene (as cis -PBI) and the corresponding conjugated polymer cis -polyPBI were developed. A fused conjugated backbone ensures good charge transport, in which the twisted polymer cis -polyPBI was found to show the highest electron mobility of 1.2 × 10 −2 cm 2 V −1 s −1 in field-effect transistors. Meanwhile, a twisted conjugated backbone effectively prevents the aggregation and crystallization of PBI units, resulting in isotropic charge transport and finely tuned micro-phase separation in bulk-heterojunction thin films. The high electron mobility and isotropic crystallinity make the fused and twisted electron acceptors achieve high power conversion efficiencies above 6% in non-fullerene solar cells, while the coplanar molecule trans -PBI as the electron acceptor shows a very low efficiency of 0.13%.